Amniotic fluid "sludge" is an independent risk factor for preterm delivery. (2nd January 2016) - Hatanaka, Alan Roberto; Mattar, Rosiane; Kawanami, Tatiana Emy Nishimoto; França, Marcelo Santucci; Rolo, Liliam Cristine; Nomura, Roseli Mieko Yamamoto; Araujo Júnior, Edward; Nardozza, Luciano Marcondes Machado; Moron, Antonio Fernandes
Abstract: Objective : To determine the prevalence and the clinical significance of amniotic fluid "sludge" (AFS) in asymptomatic patients at low and high risk for spontaneous preterm delivery. Method : A prospective cohort study was conducted on 195 singleton pregnancies at low or high risk for preterm birth (PTB) between the 16th and 26th weeks. Cervical length (CL) <25 mm and the presence of AFS were evaluated. The risk for preterm delivery before 28, 32, 35 and 37 weeks were determined according to the presence of AFS, CL < 25 mm and history of high risk for PTB. Stepwise logistic regression was performed to compare variables. Results : AFS was an independent risk factor for PTB < 35 weeks (OR: 3.08, 95% CI: 1.13–8.34, p  = 0.027) but not for PTB < 28, 32 and 37 weeks. CL < 25 mm was an independent risk factor for PTB < 28, 32 and 35 but not for PTB < 37 weeks. High risk for PTB was not found as an independent risk factor for PTB. Conclusion : AFS is an independent risk factor for PTB before 35 weeks.